Modelización hidrodinámica de una laguna costera en México - Morales, María (2020)
o understand the local hydrodynamics of the hypersaline coastal lagoon San Quintín Bay Lagoon (SQBL), located in Northern Mexico, a bidimensional modelling was applied. The lagoon presents a complex bathymetry, so the mesh was locally refined in the main channels of the lagoon. It was used wind and the seven main harmonic constants of the tide to force the model. The calibration period took place during summer 2004. The results obtained for vertical integrated velocity and sea level elevation were compared with data from three Acoustic Doppler Current Profilers placed inside the lagoon, getting a satisfactory representation of the lagoon flow dynamics with errors of 4% in elevation and a 0.96 for the correlation coefficient R 2 , while for currents the averaged error was around 12% and a correlation coefficient of 0.7 R 2 . The 2D model was capable of representing both sea level and currents inside the lagoon.